The Hebrew book in early modern Italy - Shear, Adam; Hacker, Joseph, 1940- (Jewish culture and contexts., 2011)
This volume presents new research by an international group of scholars on the history of Hebrew books in Italy from the fifteenth century to the eighteenth century, focusing on a range of issues related to the production and dissemination of Hebrew books as well as their audiences.